Role of Non-pharmacological Therapy in Children With Bed Wetting: Non-pharmacological Therapy and Bed Wetting - Rumana, Jubaida; Azmeri, Sultana; Qader, Abdul; Mohammad, Hanif (Journal of Pediatric Nephrology, 2023)
Background and Aim: Bedwetting or enuresis is not uncommon in children, although its prevalence varies by age. Spontaneous remission of enuresis may occur at a rate of approximately 15% per year, but treatment protocols should be carried out because of its significant impact on a child’s family, emotional state, self-esteem, and totally on the quality of life (QoL). Today, non-pharmacological therapy is an initial treatment for enuresis, in which both the parents and children are motivated to take the behavioral management approach. This study was done to determine the effectiveness of non-pharmacological therapy in pediatrics with enuresis. Methods: This prospective observational research was carried out in pediatrics aged 5 to 15 years with bedwetting who visited the outpatient department of Asgar Ali Hospital from January 2021 to December 2021. They were categorized into two groups, primary and secondary (monosymptomatic and non-monosymptomatic) enuresis according to the definition of the international children’s continence society (ICCS). Also, our patients were divided into different age groups: Group A: 5-7 years, group B: 8-10 years, and group C: >10 years, and the response was classified as no response: <50%, partial response: 50-99%, and complete response: 100% reduction in baseline symptom frequency. Results: Among the 74 patients, 28 cases (38%) were male and 46 cases (62%) were female, with most of them having primary enuresis 72(97%), and only two patients had secondary enuresis. Most patients were monosymptomatic 62(83.7%), and only 12 cases (16%) were non-monosymptomatic. Among 32 patients (43%) of group A, 87.5% had complete response within three months of follow-up, in group B, of a total of 20 patients (27%), 40% had complete and 40% had partial response, and in group C, among 22 patients (30%), only 9% had complete and 46% had partial response. Conclusion: Non-pharmacological therapy in enuretic patients showed encouraging recovery.